Fast low-temperature plasma reduction of monolayer graphene oxide at atmospheric pressure. (8th March 2017) - Bodik, Michal; Zahoranova, Anna; Micusik, Matej; Bugarova, Nikola; Spitalsky, Zdenko; Omastova, Maria; Majkova, Eva; Jergel, Matej; Siffalovic, Peter
Abstract: We report on an ultrafast plasma-based graphene oxide reduction method superior to conventional vacuum thermal annealing and/or chemical reduction. The method is based on the effect of non-equilibrium atmospheric-pressure plasma generated by the diffuse coplanar surface barrier discharge in proximity of the graphene oxide layer. As the reduction time is in the order of seconds, the presented method is applicable to the large-scale production of reduced graphene oxide layers. The short reduction times are achieved by the high-volume power density of plasma, which is of the order of 100 W cm −3 . Monolayers of graphene oxide on silicon substrate were prepared by a modified Langmuir–Schaefer method and the efficient and rapid reduction by methane and/or hydrogen plasma was demonstrated. The best results were obtained for the graphene oxide reduction in hydrogen plasma, as verified by x-ray photoelectron spectroscopy and Raman spectroscopy.